Statistical results on restorative dentistry experiments: effect of the interaction between main variables - Andrea Nóbrega Cavalcanti; Giselle Maria Marchi; Gláucia Maria Bovi Ambrosano (University of São Paulo, 2010)
Statistical analysis interpretation is a critical field in scientifc research. When there is more than one main variable being studied in a research, the effect of the interaction between those variables is fundamental on experiments discussion. However, some doubts can occur when the p-value of the interaction is greater than the signifcance level. OBJECTIVE: To determine the most adequate interpretation for factorial experiments with p-values of the interaction nearly higher than the signifcance level. MATERIALS AND METHODS: The p-values of the interactions found in two restorative dentistry experiments (0.053 and 0.068) were interpreted in two distinct ways: considering the interaction as not signifcant and as signifcant. RESULTS: Different findings were observed between the two analyses, and studies results became more coherent when the signifcant interaction was used. CONCLUSION: The p-value of the interaction between main variables must be analyzed with caution because it can change the outcomes of research studies. Researchers are strongly advised to interpret carefully the results of their statistical analysis in order to discuss the findings of their experiments properly.